Competitiveness of Indian bovine meat exports -- constant market share analysis - VARALAKSHMI, K; DEVATKAL, SURESH (The Indian Journal of Animal Sciences, 2017)
The present study attempts to explain the export performance of Indian Bovine meat trade and its competitiveness in International market for the period of 20 years from 1996-2014. Performance was studied using growth of exports, market shares, export shares, and source of growth was analysed by using two stage CMS analysis to decompose the growth of Indian Bovine meat exports into broad components and its sub components. It was found that overall Indian bovine meat exports registered growth rate of 13.03%, 7.94% and 22.01% in terms of quantity, price and exports value respectively. The share of India in world Bovine meat exports fluctuated and remained less than 10% for most of the years. India's bovine meat exports increased rapidly to other countries with highest overall growth of 34% while the growth of major traditional importers remained at 6.56%. The results showed that while India's market share in other countries increased, share in importing countries decreased during the study period. The results of decomposition analysis revealed that competitive effect was more significant in explaining the growth of exports. CMS analysis revealed that Bovine meat exports were more competitive in new markets in contrast to major traditional export destinations and requires emphasis. Dual strategy of penetrating in to new markets while concentrating on existing markets by increasing competitiveness will make India as major player in the world Bovine meat trade.